Constitutive Overexpression of a Conifer WOX2 Homolog Affects Somatic Embryo Development in Pinus pinaster and Promotes Somatic Embryogenesis and Organogenesis in Arabidopsis Seedlings - Hassani, Seyedeh Batool; Trontin, Jean-François; Raschke, Juliane; Zoglauer, Kurt; Rupps, Andrea (Frontiers in Plant Science, 2022)
Although full sequence data of several embryogenesis-related genes is available in conifers, their functions are still poorly understood. In this study, we focused on the transcription factor WUSCHEL-related HOMEOBOX 2 (WOX2), which is involved in determination of the apical domain during early embryogenesis and is required for the initiation of the stem cell program in the embryogenic shoot meristem of Arabidopsis. We studied the effects of constitutive over-expression of Pinus pinaster WOX2 (PpWOX2) by Agrobacterium-mediated transformation of P. pinaster somatic embryos and Arabidopsis seedlings. Over-expression of PpWOX2 during proliferation and maturation of somatic embryos of P. pinaster led to alterations in the quantity and quality of cotyledonary embryos. In addition, transgenic somatic seedlings of P. pinaster showed non-embryogenic callus formation in the root region and subsequently inhibited root growth. Over-expression of PpWOX2 in Arabidopsis promoted somatic embryogenesis and organogenesis in part of the transgenic seedlings of the first and second generation. A concomitant increased expression of endogenous, embryogenesis-related genes such as AtLEC1 was detected in transgenic plants of the first generation. The various plant phenotypes observed from single over-expressing transgenic lines of the second generation suggest some significant interaction between PpWOX2 and AtWOX2. As explanation, functional redundancy in the WOX family is suggested for seed plants. Our results demonstrate that the constitutive, high expression of PpWOX2 in Arabidopsis and P. pinaster affected embryogenesis-related traits. These findings further support some evolutionary conserved roles of this gene in embryo development of seed plants and have practical implications towards somatic embryogenesis induction in conifers.